2016
DOI: 10.1177/2380084416660672
|View full text |Cite
|
Sign up to set email alerts
|

Bioglass in Alveolar Bone Regeneration in Orthodontic Patients

Abstract: This study was designed as a split-mouth randomized controlled clinical trial to evaluate the effects of a novel bioactive glass scaffold-tailored amorphous multiporous (TAMP)for the preservation of alveolar bone following tooth extraction in class II orthodontic patients. TAMP scaffolds were prepared and sterilized. Patients were screened for eligibility, and 6 patients accounting for 14 extraction sockets were included in this stage. Sockets were randomly allocated to either control (left empty) or test (gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
(43 reference statements)
1
24
0
Order By: Relevance
“…Samples were aged at 40°C for 1 day and then soaked in ammonia solution for 3 days before they were dried and thermally stabilized at 700°C. 30 TAMP-BG was ground to a fine powder and sieved to achieve 180-300 mm particles. The preparation of (TAMP-BG) hydrogel was performed by the same method as for DAP where 5,000 mg of (TAMP-BG) powder was added to 50 mL of sterile water and then 4 g of MC powder was added to obtain TAMP-BG with 100 mg/mL concentration.…”
Section: Antimicrobial Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were aged at 40°C for 1 day and then soaked in ammonia solution for 3 days before they were dried and thermally stabilized at 700°C. 30 TAMP-BG was ground to a fine powder and sieved to achieve 180-300 mm particles. The preparation of (TAMP-BG) hydrogel was performed by the same method as for DAP where 5,000 mg of (TAMP-BG) powder was added to 50 mL of sterile water and then 4 g of MC powder was added to obtain TAMP-BG with 100 mg/mL concentration.…”
Section: Antimicrobial Preparationmentioning
confidence: 99%
“…In addition to being biocompatible, TAMP-BG has been previously shown to enhance hard tissue regeneration in a recently published clinical trial. 30 This fact coupled with the demonstrated antimicrobial properties of TAMP-BG may further urge this material to be used as a potential scaffold for dentin/pulp regeneration for REPs. 60 Also, this is the first study to use TAMP-BG suspended in water soluble vehicle (MC). This form was used to ease the delivery and removal of TAMP-BG rather than using it as a slurry paste and also to enhance TAMP-BG degradation and liberation of Ca, Si, and P ions.…”
Section: Assessment Of the Residual Biofilm Structure (Sem Analysis)mentioning
confidence: 99%
“…Moreover, in a clinical trial to evaluate the effect of bioactive glass scaffold for the preservation of alveolar bone following tooth extraction, it was found that bioactive glass scaffolds appeared to enhance the recruitment of stem cells from the grafted sockets. They concluded that bioglass scaffolds appeared to preserve alveolar bone following extraction and allow for a more active bone modeling and remodeling process (38) .…”
Section: Discussionmentioning
confidence: 99%
“…In another clinical study, bioactive glass having both nanopores and micropores showed that alveolar bone remodeling was improved at the pocket resulting from tooth extraction. The addition of nanopores within the structure contributed to increase the surface area and therefore, to the dissolution whose products participate in the remodeling process [ 230 ]. A SAP-based hydrogel named P 11 -4 showed to behave as a nucleation agent in the formation of hydroxyapatite and showed in caries lesion treatments, enamel regeneration in humans [ 231 ], this same system also promoted regeneration of rat bone cranial defects after 6 weeks [ 232 ].…”
Section: In Vivo Outcomes and Clinical Trialsmentioning
confidence: 99%